Online Student Advisory System - Hashim, Norfazila (Universiti Teknologi Petronas, 2005)
The advancement oftechnology provides massive benefit to human beings. With the aid oftechnology, many things that were lately thought impossible are now made possible such as internet. This project related to the internet application, is called Online Student Advisory System, Currently in most university is using traditional or manual student advisory process and procedure which hold responsible to be tedious and time consuming. Alternatively there is rising trend in implementing online student advisory system that potentially better. The goal of this project is to come out withmore efficient and effective student advisory system. Along the way, few objectives and scope ofstudy have been set up which are to provide SMS alert system, enable user to track the activities performed, allow messaging and submitting report online. The project should minimize thus saving energy and time directed by all personnel involves in this advisory system in order to be more effective. The development ofthis project will follow Rapid Application Development (RAD) methodology which consists of four phases; Requirements and Planning, User Design, Construction and Cutover phase. Implementation and accomplishment of this project can positively be stepping-stone toward development of actual Online Student Advisory System in most university. Importance finding of this project is level of response and acceptance of usertoward the development of online student advisory system.